Importance of flowers in field margins for insect communities in agroecological farms from Cordoba, Argentina - Rojas Rodriguez, Josefina; Rossetti, Maria Rosa; Videla, Martín (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
Field margins are key factors for biodiversity conservation in agroecological farms. Insect communities are involved in crucial services such as pollination and biological control of pests and they can use floral resources in the margins. In this study we examine spatial and temporal variation of floral communities in margins of agroecological farms from Cordoba and insect abundance in function of taxonomic identity, temporal availability, local abundance and origin (native vs. exotic) of floral resources. We carried out two samplings per month during summer season in the field margins in which we identified floral species and insects on flowers. We registered 57 floral species (41 native and 16 exotic). Temporal variations in abundance and richness of flowers were not significant, while the composition varied according to the sites. Insects included 9 orders and their abundance increased with floral period of species and this increment was stronger for exotic plants. These results indicate that the borders of spontaneous vegetation represent habitats with a high conservation value, being key to study aspects such as phenology and functional diversity of flowers and insects to increase the provision of ecosystem services in agroecological farms.